Assessing Pre-Service Secondary Mathematics Teachers' Attitude Towards Geometer's Sketchpad - Chew, Cheng Meng (Penerbit Universiti Sains Malaysia, 2012)
The purpose of this study was to assess pre-service secondary mathematics teachers' attitude towards Geometer's Sketchpad (GSP) following an introductory GSP workshop. GSP is a dynamic geometry software program used for constructing and investigating mathematical objects. It is a dynamic tool for construction, demonstration and exploration of mathematical objects, adding a powerful dimension to the study of geometry and many other areas of mathematics. A total of 107 pre-service secondary mathematics teachers who attended a mathematics teaching methods course in a local public university participated in the GSP workshop. None of the participants had any prior experience using GSP. Analysis of their responses to the "Geometer's Sketchpad Attitude Scales" indicated that the pre-service secondary mathematics teachers showed a positive attitude towards GSP is more appropriate because the ''Geometer's Sketchpad Attitude Scales'' was used to access the participants' attitude towards GSP. The results also indicated that there was no significant difference between male and female preservice secondary mathematics teachers in their overall attitude towards GSP is more appropriate because the ''Geometer's Sketchpad Attitude Scales'' was used to access the participants' attitude towards GSP. Implications of the study for conducting GSP workshops in mathematics teaching methods courses are discussed.